Ground Zero : in-depth stories from across India - Suresh Nambath Ed (Chennai THG Publishing Private Ltd, 2025)
CONTENTS: 1. On your marks, get help,go, 2. Betrayed by blind faith, 3. Casting the net in a sea of conflict, 4. In shrinking habitats, desperate cats, 5. When the mountains had a meltdown, 6. Calamity in the capital, 7. An IT hub and its struggle for healthcare, 8. Invading virus, ill-equipped villages, 9. Turning the COVID-19 tide in Chennai, 10. Persecuted in Pakistan, ignored in India, 11. A village basking in vaccine glory, 12. Ending the shift between Jammu and Kashmir, 13. The vaccine scamster of Kolkata, 14. The city of dreams' unending nightmare, 15. The complex story of rising cases in Kerala, 16. In Haryana, taking the mat by storm, 17. A People who bacame Indian overnight, 18. How the lawe caught up with an artful dodger, 19. A missing baby and a flustered state, 20. In Kashmir, a throwback to the '90s, 21. A Christmas of grief in Mon. 22. Inside Kerala's spiral of revenge politics, 23. The young, educated hatemongers, 24. Headscarf and a social fabric in tatters, 25. The people caught between two States, 26. How to steal an iron bridge, 27. An industry barely hanging by a thread, 28. Faith, caste, patriarchy, and murder, 29. In Seoni, the blood trail of a lynching, 30. When guns and lives go for a song, 31. Where peace hangs by a thread, 32. Fishing in urcertain waters, 33. Being Sarna: a fight to define tribal identity, 34. Token prohibition takes a toll in Gujarat, 35. Three murders in a communal cauldron, 36. From darkness to solar-powered light, 37. Delays, debt and distress in West Bengal, 38. Where the stars must not twinkle, 39. The macabre murders in Elanthoor village, 40. Air bubbles in Delhi's dystopia, 41. Forging a connect along the Ghats, 42. Fear and foreboding in Joshimath, 43. On the shifting banks of tghe Ganga, 44. Invisible boundaries, visible apathy,45. A Jumbo problem in Hassan district, 46. Breathing the toxic air of Chandrapur,47. In Punjab, fear of the return of 'dark days', 48, Left high and dry in the Nilgiris, 49. Kalakshetra's summer of discontent, 50. The rise and fall of Atiq Ahmed, 51. The growing problem of substance abuse in J&K, 52. As vigilante groups thrive, couples try to survive, 53. Tragedy on the tracks, 54. Bleeding blue in Nanded, 55. Facing the heat, 56. The Infinite variety of custom, 57. Bombs and ballot boxes, 58. In an armed conflict, the war on women, 59. In the shadow of the Millennium City, 60. Ragging rage, 61. Kota's crash course, 62. Nipah puts Kerala under siege again, 63. The river runneth over, 64. Odourless, tasteless, lethal: thallium as a murder weapon, 65. Stubble trouble, 66. Uncertain future in a sea of poppies, 67. Trapped in the Himalayas, 68. A city under water, 69. Intruders in Parliament, 70. Weddings, guns, funerals, 71. Dream destination, nightmarish journey, 72. The babies branded with hot bangles.
Keywords: Investigative Journalism India; Social Issues and Human rights Reportage